2021
DOI: 10.3847/1538-4357/abf64b
|View full text |Cite
|
Sign up to set email alerts
|

TeV Emission of Galactic Plane Sources with HAWC and H.E.S.S.

Abstract: The High Altitude Water Cherenkov (HAWC) observatory and the High Energy Stereoscopic System (H.E.S.S.) are two leading instruments in the ground-based very-high-energy γ-ray domain. HAWC employs the water Cherenkov detection (WCD) technique, while H.E.S.S. is an array of Imaging Atmospheric Cherenkov Telescopes (IACTs). The two facilities therefore differ in multiple aspects, including their observation strategy, the size of their field of view, and their angular resolution, leading to different analysis appr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…HAWC measures a higher flux than IACT experiments. Differences in the field-of-view, angular resolution, and background estimation methods between IACTs and HAWC contribute to discrepancies in the measured flux (Abdalla et al 2021). HAWC uses a background estimation method called "direct integration" (Atkins et al 2003).…”
Section: Comparison To Other Experimentsmentioning
confidence: 99%
“…HAWC measures a higher flux than IACT experiments. Differences in the field-of-view, angular resolution, and background estimation methods between IACTs and HAWC contribute to discrepancies in the measured flux (Abdalla et al 2021). HAWC uses a background estimation method called "direct integration" (Atkins et al 2003).…”
Section: Comparison To Other Experimentsmentioning
confidence: 99%
“…It corresponds to events triggering more than 25% of the array, which gives an energy threshold of approximately 1 TeV. For this specific bin selection, the sources 3HWC J1928+178 is refered to as HAWC J1928+178 in [2]. The corresponding PSF of the instrument is ∼0.4°for bin 4 and decreases to less than 0.2°for bin 9.…”
Section: The Hawc Observatory and Hawc Datamentioning
confidence: 99%
“…This choice is motivated by the fact that 3HWC J1930+188 was detected as a point-like source by HAWC, H.E.S.S. [4] and VERITAS [5], and by previous studies of 3HWC J1928+178 that showed that it is likely extended [2] [10]. A simple power law dN/dE = F 0 (E/E 0 ) Γ is assumed as energy spectrum for all components.…”
Section: The Four Components Modelmentioning
confidence: 99%
See 2 more Smart Citations